Adoption of artificial intelligence (AI) and its influence on financial reporting and disclosure: A Malaysian empirical study - Ramasamy, Meenah; Palanimally, Yamuna Rani; Mohamad, Zam Zuriyati; Johanthan, Sonia; Abdul Razak, Rizalniyani; Saundra Rajan, Dinesh Kumar (International Journal of Accounting, Finance and Business, 2025)
The rapid advancement of Artificial Intelligence (AI) has transformed business operations globally, including the field of accounting and financial reporting. In Malaysia, the integration of AI into financial reporting processes remains an emerging practice, with limited empirical evidence regarding its impact on reporting quality and disclosure. This study investigates the adoption of AI in Malaysian organisations and examines its influence on financial reporting accuracy, timeliness, completeness, and transparency. A mixed-methods approach is employed, combining quantitative surveys of 200 finance professionals and auditors with qualitative interviews of 25 key stakeholders, including management, auditors, and investors. The findings indicate that AI adoption significantly enhances reporting quality by automating routine tasks, detecting anomalies, and enabling predictive analytics. However, implementation is constrained by factors such as high costs, limited technical expertise, regulatory uncertainty, and organisational resistance to change. Stakeholders perceive AI as a valuable tool for improving disclosure effectiveness and decision-making, but emphasise the need for robust governance frameworks and human oversight to mitigate risks. This study contributes to the theoretical understanding of technology adoption in accounting, provides practical insights for Malaysian firms, and offers policy recommendations for regulators to facilitate AI integration in financial reporting. The results have implications for firms seeking competitive advantage through digital transformation while maintaining compliance with Malaysian Financial Reporting Standards (MFRS) and ensuring stakeholder trust.